Gastrointestinal Operations and Technical Variations - Korenkov, Michael; Germer, Christoph-Thomas.; Lang, Hauke; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book is exceptional in describing not only the standard surgical procedures, open and laparoscopic, for various gastrointestinal indications, but also the technical variations that may be employed in response to difficult intraoperative situations. For each surgical procedure, leading experts provide step-by-step, illustrated descriptions of their standard techniques and preferred modifications when confronted by challenging circumstances associated with an increased risk of intra- or postoperative complications. All of the described variations are designed to meet the original surgical goals and achieve satisfactory outcomes. Topics addressed include upside-down stomach, antireflux surgery, gastric gastrointestinal tumors, gastric cancer, gallbladder and bile duct disease, inflammatory bowel disease, right and left hemicolectomy, sigmoid diverticulitis, rectal cancer, and rectal prolapse. The provision of several points of view for each surgical indication ensures that approaches from the conservative to the more radical are conveyed. It is clearly explained in which situations use of the described technical variations may be indicated, and practical tips are provided on the avoidance of complications. In addition, important medicolegal issues are discussed and guidance is offered on risk assessment and decision analysis within the surgical setting. This book will be an invaluable aid to decision making and practice for every gastrointestinal surgeon.
The basics -- Individual surgery for upside down stomach and antireflux surgery -- Individual surgery for gastric gastrointestinal stromal tumors -- Individual surgery for gastric cancer -- Individual surgery for benign gallbladder and bile ducts diseases -- Individual surgery for inflammatory bowel disease -- Individual surgery for right hemicolectomy -- Individual surgery for left hemicolectomy -- Individual surgery for sigmoid diverticulitis -- Individual surgery for rectal cancer -- Individual surgery for rectal prolapse.
Keywords: Medicine; Abdominal surgery; Surgery; Medicine & Public Health; Abdominal surgery; General Surgery